Preoperative Renal Artery Embolization Before Radical Nephrectomy for Nonmetastatic Renal Cell Carcinoma: A Propensity Score Matched Analysis - Jin Noh; Sang Hun Song; Gyoohwan Jung; Sangchul Lee; Sung Kyu Hong; Seok Soo Byun; Jung Kwon Kim (Journal of Urologic Oncology)
Purpose This study investigated the effects of preoperative renal artery embolization (PRAE) before radical nephrectomy (RN) for advanced nonmetastatic renal cell carcinoma (RCC) on perioperative and oncologic outcomes. Materials and Methods We analyzed 820 patients who had undergone RN for advanced nonmetastatic RCC (cT3-4/N0-1) between June 2003 and May 2022. Propensity score matching (PSM) at a 1:2 ratio was performed using the nearest-neighbor method, matching 121 PRAE patients to 242 controls. The primary endpoints included recurrence rate, overall survival, cancer-specific survival, and recurrence-free survival. Results Before PSM, there were differences in sex (p=0.047), clinical stage (p=0.001), and the Fuhrman grade (p<0.001) between the 2 groups. After PSM, the baseline characteristics were well balanced. The mean age at operation was 58.2±13.0 years, and the median follow-up was 42.0 months. The postoperative transfusion rate was higher in PRAE group (18.2% vs. 10.7%, p=0.049). No significant differences were found between the PRAE and control groups in operation time (166.6±95.3 minutes vs. 155.5±74.2 minutes, p=0.263), estimated blood loss (360.4±732.0 mL vs. 293.4±596.6 mL, p=0.384), or length of hospital stay (7.7±4.9 days vs. 7.7±3.7 days, p=0.961) between the 2 groups. Recurrence was significantly less common in the PRAE group than in the control group (20.7% vs. 34.3%, p=0.007). No significant differences were found in cancer-specific death (8.3% vs. 9.1%, p=0.793) or overall death (8.3% vs. 12.0%, p=0.281). In multivariate logistic regression analysis, clinical T stage ≥3 (odds ratio [OR], 4.365; p<0.001), clinical N stage 1 (OR, 2.405; p=0.020) and no PRAE (OR, 2.293; p=0.004) were independent predictors of recurrence. Conclusions Our results showed that PRAE was related to a lower recurrence rate. Thus, PRAE seems to be useful before RN for nonmetastatic RCC patients.